2012
DOI: 10.1186/1471-2474-13-163
|View full text |Cite
|
Sign up to set email alerts
|

Important risk factors and attributable risk of vertebral fractures in the population-based Tromsø study

Abstract: BackgroundVertebral fractures, the most common type of osteoporotic fractures, are associated with increased risk of subsequent fracture, morbidity, and mortality. The aim of this study was to examine the contribution of important risk factors to the variability in vertebral fracture risk.MethodsVertebral fracture was ascertained by VFA method (DXA, GE Lunar Prodigy) in 2887 men and women, aged between 38 and 87 years, in the population-based Tromsø Study 2007/2008. Bone mineral density (BMD; g/cm2) at the hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
(65 reference statements)
4
20
0
6
Order By: Relevance
“…As prevalence rates of daily smoking also have been shown to be inversely correlated to education in Europe [17], the lower examination rates among smokers is a contributing factor to inequalities in health in Norway. The prevalence of smoking in the study population was in concord with reported rates from the Tromsø VI study [18], even though they were lower than findings from the Statistical Bureau of Norway [19], with reported rates of active smoking of 21 % among both men and women in 2008. However, they were higher than reported rates from other cohorts investigating fracture risk such as the COSHIBA cohort [20], a cohort of females from Puerto Rico [21], the Heartfordshire cohort [22] as well as a regional cohort from Spain [23], even though Norway is known for a restrictive public smoking policy.…”
Section: Discussionsupporting
confidence: 70%
“…As prevalence rates of daily smoking also have been shown to be inversely correlated to education in Europe [17], the lower examination rates among smokers is a contributing factor to inequalities in health in Norway. The prevalence of smoking in the study population was in concord with reported rates from the Tromsø VI study [18], even though they were lower than findings from the Statistical Bureau of Norway [19], with reported rates of active smoking of 21 % among both men and women in 2008. However, they were higher than reported rates from other cohorts investigating fracture risk such as the COSHIBA cohort [20], a cohort of females from Puerto Rico [21], the Heartfordshire cohort [22] as well as a regional cohort from Spain [23], even though Norway is known for a restrictive public smoking policy.…”
Section: Discussionsupporting
confidence: 70%
“…Prior fracture is a secondary indication (when combined with age) in the 2007 ISCD indications for VFA, (11) and BMI has been identified in some studies (13, 15, 17, 20), but not others (18, 21, 22), as a risk factor for vertebral fracture. Other studies have identified back pain to be associated with PVFx in women,(22, 3235) and two have identified grip strength as to be associated with PVFx.…”
Section: Methodsmentioning
confidence: 99%
“…(11) While many risk factors have been shown to be independently associated with PVFx in multivariable-adjusted regression models,(1222) only a few of these studies included significant numbers of men. (18, 2123) Moreover, studies to date have not investigated whether or not prediction models incorporating most or all of these risk factors perform better than more parsimonious models that might be easier to implement in clinical practice. Additionally, it is unclear if regression-based prediction models more accurately discriminate men with from men without PVFx than simple lists of indications for lateral spine imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Prior non-vertebral fracture, BMI, grip strength, and self-reported back pain were included in a third, more complex model. Prior fracture is a secondary indication (when combined with age) in the 2007 ISCD indications for VFA,(9) and BMI has been identified in some studies(10, 12, 14, 17), but not others(15, 18, 19) as a risk factor for vertebral fracture. Other studies have identified back pain to be associated with prevalent vertebral fractures in women,(19, 27, 28) and two have identified grip strength as to be associated with PVFx.…”
Section: Methodsmentioning
confidence: 99%